Impasses e saídas: o amor em contos de Lygia Fagundes Telles - Alves, Paula Rúbia Oliveira do Vale (2014)
This research intends to show the psychological complexity of the Lygia’s characters starting from the different ways they use to deal with the suffering that arises from heartbreaks. To reach such goal it has been used Lygia Fagundes Telles’ storybooks, interviews and testimonials, also academic papers and literary essays about her work besides theoretical texts: Denis de Rougemont, Bauman, Stendhal, Comte-Sponville, Freud and Lacan, among others. The corpus of this dissertation consists of 8 stories by the author, analysed in two chapters entitled: Love and rejection in female characters and The love and its deadlocks in male characters. The female characters Kori (Você não acha que esfriou?), Pomba Enamorada (homonymous story) and Alice (Emanuel) suffer from being rejected and Maria Camila (Um chá bem forte e três xícaras), from the fear of also being rejected in the future; the reactions vary between vengeance, fantasy, delirium and facing the situation. The suffering of the male protagonists come from betrayal (the saxophone man); from abandonment (Ricardo from Venha ver o pôr-do-sol); indecision (Miguel from O Noivo); and contempt (the redhead man from História de Passarinho) and the outputs presented gravitate around sublimation/sadism, murder, forgetfulness and escape. It was observed that in female characters the loving suffering comes, mainly, from rejection, differently from the male characters whose cause for suffering is variable and the outputs present to be more radical. The different ways how female and male characters go through the love impasses created interest of deepen the theme of gender differences, what is only superficially discussed in this paper. This study confirms the psychological complexity of Lygia’s characters whose analyses point to unconscious motivations underlying attitudes, thoughts and feelings, all suggested in the interstices of the text, allowing many reflections about real characters and their positions on issues of love.